Cultivo in vitro de Pyrus sp., cultivares Carrick, Cascatense e Ya-Li - Silva, Ilda Mariclei de Castro da (2013)
In Brazil, among the temperate climate fruit, the pear (Pyrus sp.) is the third more commonly consumed although most of it is imported (95%) as its cultivation is still in small-scale. The lack of cultivars adapted to the soil and climate conditions of potentially productive regions is the main obstacle for its sustainable production, as these cultivars need to be apt to produce in regularly, with a considerable quality and amount to supply the demand of the of the internal market. Mutation induction techniques, such as the use of gamma radiation, have been quite efficient in the production of genetic variability and, thus, are very used in improvement programs of several species of plants. In pear trees, due to the little genetic variability, long cycles and cross-pollination, characteristics which make it more difficult to obtain new cultivars through the conventional improvement, the usage of the gamma radiation may fulfill these difficulties. This technique, along the tissue culture is an alternative which enables the development of specific cultivars, in a short term, in large scale and with a high health quality. However, to help the usage of in vitro propagation it is necessary to obtain propagation protocols. In this context, the present work aimed to optimize the in vitro and ex vitro cultivation of three pear cultivars (Pyrus sp.): Carrick, Ya-Li and Cascatense (a cultivar recently launched by the Genetic Improvement Program from Embrapa Temperate Climate), in order to foster its production and the mutations induction, aiming to select new genotypes with interest characteristics, from the original genotypes. The study was conducted in experiments which focused on multiplying in vitro the cultivar mentioned above, as well as radiate and, from this, micropropagation the cv. Ya-Li. For the carrying out of the experiments, nodal segments were used (1,0 cm) with two to three axilliary gems. To reach an efficient protocol of multiplication in vitro, the explants were inoculated in different cultivation means and salt concentrations, BAP and sucrose. To check the effects of different dosage of gamma radiation (0, 10, 20, 30 and 40 Gy) during the micropropagation, were carried experiments out of multiplication and rooting in vitro and aclimmatization. The results obtained showed that the multiplication in vitro of the cultivar Carrick can be fostered by using MS commercial Himédia, with supplementation of 1,2 mg L-1 of BAP and 30 g L-1 of sucrose, while the most appropriate mean for the multiplication in vitro of the cultivar Ya-Li is the MS, with 1,2 mg L-1 of BAP and 45 g L-1 of sucrose. For the Cascatense‟, the MS Himédia, supplemented by 0,8 mg L-1 of BAP and 30 g L-1 of sucrose presented the best responses. Concerning the use of irradiation, the gamma radiation led to morphological changes in the explants of the cultivar Ya-Li, during the micropropagation, being that these might be due to epigenetic and/or genetic (inheritable) changes. Thus, based on the results of this study, due to obtaining high rates of in vitro multiplication from the optimization of protocols, it appears that is possible to multiply the three cultivars on a large scale, as well as possible to obtain mutants of cv. Ya-Li via gamma radiation. However, to determine whether the morphological changes found are positive or negative and is transmitted by the progeny, although future research is needed in the materials obtained.